Seasonality and disturbance: annual pattern and response of the bacterial and microbial eukaryotic assemblages in a freshwater ecosystem - Adriane Clark Jones; T. S. Vivian Liao; Fares Z. Najar; Bruce A. Roe; K. David Hambright; David A. Caron (Environmental Microbiology, 2013)
Summary High‐throughput pyrosequencing of SSU rDNA genes was used to obtain monthly snapshots of eukaryotic and bacterial diversity and community structure at two locations in L ake T exoma, a low salinity lake in the south central U nited S tates, over 1 year. The lake experienced two disturbance events (i) a localized bloom of P rymnesium parvum restricted to one of the locations that lasted from J anuary to A pril, and (ii) a large (17 cm), global rain event in the beginning of M ay, overlaid onto seasonal environmental change. Eukaryotic species richness as well as both eukaryotic and bacterial community similarity exhibited seasonal patterns, including distinct responses to the rain event. The P . parvum bloom created a natural experiment in which to directly explore the effects of an E cosystem D isruptive A lgal B loom ( EDAB ) on the microbial community separated from seasonal changes. Microbial species richness was unaffected by the bloom, however, the eukaryotic community structure (evenness) and the patterns of both eukaryotic and bacterial community similarity at bloom and non‐bloom sites were statistically distinct during the 4 months of the bloom. These results indicate that physical and biological disturbances as well as seasonal environmental forces contribute to the structure of both the eukaryotic and bacterial communities.